Exopolysaccharide-Derived Carbon Dots for Microbial Viability Assessment - Lin, Fengming; Li, Chengcheng; Chen, Zhan (Frontiers in Microbiology, 2018)
Fluorescent dye staining combined with fluorescence microscopy or flow cytometry is becoming a routine way to monitor microorganism viability that is necessary for food safety, antibiotic development and human health. However, the conventional live/dead assay dyes suffer from high cost, inconvenient staining steps, and high cytotoxicity, which is urgently needed to overcome. Herein, cheap carbon dots, CDs-EPS605, were reported to successfully assess microbial viability in a convenient way with neglectable cytotoxicity. The fluorescent N-doped CDs-EPS605 could be facilely prepared from bacterial amino exopolysaccharide (EPS) by one-step hydrothermal carbonization, which is cost-effective and sustainable. The negatively charged CDs-EPS605 consisted of C, H, O, N, P, and S, and featured various functional groups, including -COOH, -OH, -CONH-, and -NH2. CDs-EPS605 were observed to sensitively and selectively stain dead microorganisms instead of live ones to enable discrimination of live/dead microorganisms. The labeling method with CDs-EPS605 did not require protection from light, or washing, which is convenient. Additionally, CDs- EPS605 displayed better photostability and much less cytotoxicity compared to the commercial counterpart. Altogether, CDs-EPS605 represent a simple, yet powerful staining agent for microbial viability assessment, and at the same time enrich the current applications of microbial EPS.